Analysis Of Cloud Computing Usage In Vocational School Environment Using Delone MClean - Wasiran, Wasiran; Setiawan, Antonius Darma; Arif, Yanuar Zulardiansyah (International Journal of Computer and Information System (IJCIS), 2022)
Data is very important. In today's era, any activity will involve data. Likewise, schools of course have large piles of data. A lot of data needs to be stored so that it can be managed better, the storage certainly requires a computer system in the form of a server. The server itself has several types that can be used, one of which is a local server and a cloud server. Of the several types of servers, of course, there are many variants of servers that are applied by agencies, especially in this case educational institutions or schools. In this study, several secondary schools were taken to compare which one had a higher success rate of implementation. The analysis was carried out using the Delone MClean method. The result is that the implementation of local servers has a higher success rate than cloud servers.